STRATEGI PEMASARAN PERBANKAN SYARIAH UNTUK MENARIK MINAT MENABUNG MASYARAKAT MILENIAL - Riska Aulia Riska; Hasbullah Hasbullah (Universitas Mitra Indonesia, 2023)
Marketing issues are an obstacle for Islamic banking. This has an impact on the low public interest in Islamic banking services. The lack of socialization to the community has resulted in people still tending to entrust all their financial activities to conventional banks. Marketing strategy is the spearhead for banks to introduce and market excellence products. In this terbaru era, the strategy in marketing products must be more adaptable, especially to the millennial community. Today's society cannot be separated from the digital world and social media, almost all of their activities involve digital. applied in increasing public interest must also be developed so that all levels of society can recognize the products offered more easily. This encourages researchers to conduct further research, one of which concerns the marketing aspect.